Onabotulinumtoxin‐A in Chronic Migraine: Should Timing and Definition of Non‐Responder Status Be Revised? Suggestions From a Real‐Life Italian Multicenter Experience. Issue 8 (27th August 2019) - Vernieri, Fabrizio; Paolucci, Matteo; Altamura, Claudia; Pasqualetti, Patrizio; Mastrangelo, Vincenzo; Pierangeli, Giulia; Cevoli, Sabina; D'Amico, Domenico; Grazzi, Licia
Abstract : Objective: To clarify whether the clinical response after the first 2 cycles with Onabotulinumtoxin A can accurately predict the long‐term response. Background: Onabotulinumtoxin‐A (OBT‐A) is an approved preventive treatment option for chronic migraine (CM). Nowadays, it remains to be clarified if the treatment has to be prolonged for at least an entire year (4 injections every 3 months – ie, quarterly, as proposed in the PREEMPT trials) or it can be halted after the second or third injection if not clinically effective. Design and Methods: We conducted a multicenter observational cohort study based on real‐life data on the usage of OBT‐A in CM patients from 2 Italian headache centers, Roma Campus Bio‐Medico and Milano Besta, adopting the whole 4‐injections protocol. We performed a retrospective analysis of medical records of consecutive patients treated in the 2 centers. The main statistical analysis aimed to evaluate longitudinal measures related to headache (monthly headache frequency, monthly number of analgesic drugs, MIDAS). We hypothesized from our clinical practice with OBT‐A that only 2 cycles of treatment were not enough to actually define the non‐responder status to botulinum toxin A and that probably a longer time of treatment is needed to get the condition of long‐term (delayed) responder. Results: We considered 115 patients from the 2 centers: 53 in Roma and 62 in Milano. Regarding the main analysis, a clear improvement in each measure was obtained at the 6 months assessment and maintained up to 12 months. Comparing patients with <30% and ≥30% reduction in headache frequency between T0 and T2 or T4 (respectively, "Non‐Responders" and "Responders"), we found that the agreement between the classification Responders/Non‐Responders at T2 and T4 was not very high (79/104 = 76.0%, with a "moderate" Cohen's Kappa of 0.51), suggesting that the status at T4 is not fully predictable by the status at T2 ( λ = 0.47). Responders for headache frequency at T4 were 54.8%. Among Responders at T2, Responders at T4 were 47/62 = 75.8% (95% CI: 64.5%, 85.5%), while among Non‐Responders at T2, Responders at T4 were 10/42 = 23.8% (95% CI: 11.9%, 38.1%). Similarly, even when considering the 50% reduction in painkillers consumption or in MIDAS total score between T0 and T2 as possible prognostic factors, the changes occurring at T4 are not strongly predictable by those at T2. Conclusions: A ≥30% reduction in headache frequency at T2 cut‐off is not adequate in predicting a late response to treatment: more than a quarter of excluded patients would miss a clinical improvement with an ongoing treatment, while in a similar percentage of Responders the treatment would lose efficacy. Results from our real‐life study suggest that we possibly have to postpone the definition of Responder/Non‐Responder to OBT‐A at least after 1 year of treatment (4 cycles).